2021
DOI: 10.3389/fphar.2021.780940
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ceftazidime-Avibactam Versus Polymyxin B and Risk Factors Affecting Clinical Outcomes in Patients With Carbapenem-Resistant Klebsiella pneumoniae Infections a Retrospective Study

Abstract: Background: The worldwide outbreak of carbapenem-resistant Klebsiella pneumoniae (CRKP) has become an urgent public health problem. High mortality and lack of effective treatments further pose new challenges to control this infection. However, studies about the evaluation of available antibiotics for CRKP infection are limited. The present study aimed to compare the efficacy of polymyxin B versus ceftazidime-avibactam (CAZ/AVI) in Chinese patients with CRKP infections and to identify risk factors affecting 7-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 47 publications
(49 reference statements)
3
25
0
Order By: Relevance
“…The results from our study also showed that patients who received CAZ/AVI-based antimicrobial therapy would have a significantly higher probability of CRKP clearance than those receiving PMB-based antimicrobial therapy in vivo, which was consistent with the conclusion of Fang et al’s article [ 5 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results from our study also showed that patients who received CAZ/AVI-based antimicrobial therapy would have a significantly higher probability of CRKP clearance than those receiving PMB-based antimicrobial therapy in vivo, which was consistent with the conclusion of Fang et al’s article [ 5 ].…”
Section: Discussionsupporting
confidence: 91%
“…Several in vitro and in vivo studies have discussed the effectiveness of CAZ/AVI and PMB, which proved that these two agents were both reliable treatment options for patients with CRKP infections [22][23][24][25]. Fang et al drew the conclusion that CAZ/AVI-based therapy was more effective than PMB-based therapy in treating CRKP infection by implementing a retrospective analysis to compare the efficacy between these two therapies [5]. Nevertheless, suitable therapeutic combined agents with CAZ/AVI remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…41 Furthermore, several previous retrospective studies have supported the superiority of CAZ/AVI in the treatment of CRKP infection. [42][43][44] Given the modest number of patients who received CAZ in the current study, the efficacy of CAZ/AVI in patients with CRKP BSI needs to be confirmed in larger-scale trials.…”
mentioning
confidence: 99%